Polymer-modified screen-printed electrode-based electrochemical sensors for doxorubicin detection - Iva Dimitrievska, Perica Paunovikj, Anita Grozdanov (The Association of South-East European Electrochemists (ASEEE), 2025)
In the last decade, intensive research has been performed in the field of analytical electrochemistry, seeking designs of electrochemical sensors capable of providing better analytical characteristics in terms of sensitivity, selectivity, reliability, ease of fabrication and use, and low cost, especially for pharmaceutical drug monitoring. Our research has primarily focused on developing screen-printed electrode-based sensors and their application as electrochemical platforms for drug determination and monitoring, specifically emphasizing their suitability for surface modification. A commercial screen-printed graphene electrode was used as the electrochemical sensing component, which was subsequently modified with polymers, such as polyvinylidene fluoride and chitosan. All studied electrodes were tested using a doxorubicin hydrochloride (DOX) solution with a concentration of 0.002 mol L-1 dissolved in 0.1 mol L-1 phosphate-buffered saline at pH 6.7. Cyclic voltammetry was used as an electrochemical characterization technique to gather data on all tested electrodes' electrochemical activity. The morphological characterization of the electrodes was done using scanning electron microscopy. The changes in the electrolyte during the electrochemical measurements were followed through ultraviolet-visible spectroscopy. The modified electrodes demonstrated a favorable electrochemical response to DOX and exhibited higher electrical conductivity than the commercial one. The characterization results indicated that the Ch-modified electrode exhibited excellent electrochemical conductivity and demonstrated strong electrochemical performance. The evaluations of this electrode comprised the definition of the lowest limit of detection and limit of quantification among the tested electrodes, with values of 9.822 and 32.741 µmol L-1, respectively, within a linear concentration range from 1.5 to 7.4 µmol L-1. Additionally, the electrodes showed excellent repeatability, stability, and reproducibility, confirming their suitability for sensitive DOX detection.
Keywords: Graphene; polyvinylidene fluoride; chitosan; anticancer medication, sensing